Serous Tubal Intraepithelial Lesions: Clinical Case Report and Literature Review - Tretjakova, Ksenija; Bužinskienė, Diana (Lietuvos chirurgija, 2025)
Serous tubal intraepithelial lesion (STIL) is a rare benign lesion of the fallopian tube epithelium characterized by atypical epithelial cells with morphological anomalies, marked by the accumulation of p53 protein and normal or slightly increased proliferative activity. STIL is becoming an increasingly investigated type of fallopian tube neoplasm, with differential STIL diagnosis based on the morphology of the fallopian tube epithelium and immunohistochemical markers p53 and Ki-67. Benign intraepithelial changes of the fallopian tube occur in the distal third of the tube and are considered precursors to serous tubal intraepithelial carcinoma (STIC), which ultimately progresses to high-grade serous ovarian cancer (HG-SOC). More precise methods for investigating the fallopian tubes are emerging to detect epithelial changes and neoplasms as early as possible. So far, there are no accurate prognoses for this pathology or recommendations for the further monitoring and treatment of patients.
Keywords: Serous tubal intraepithelial lesions; STIL; Benign Fallopian Tube Neoplasms